Perdagangan Manusia di Balik Layar Aplikasi: Pelajaran Hukum dari Kasus MiChat - Ajeng Yuni Astari (Jurnal Hukum Lex Generalis, 2025)
This study examines the phenomenon of misuse of the MiChat application as a means of online prostitution practices that have the potential to fall into the category of human trafficking (TPPO) crimes. The MiChat application, with its anonymous features and location-based search, facilitates perpetrators to offer sexual services online, which poses new challenges in law enforcement in the digital era. This study aims to analyze how the law in Indonesia, especially Law Number 21 of 2007 concerning the Eradication of TPPO and Law Number 19 of 2016 concerning Information and Electronic Transactions (UU ITE), regulates and responds to this phenomenon. The research method used is a normative legal approach with a case study, which involves an analysis of relevant laws and court decisions related to online prostitution cases through the MiChat application. Data were collected through literature reviews and legal documentation, and analyzed to understand the application of the law in practice and identify gaps between theory and implementation. The results of the study indicate that the use of the MiChat application as a means of online prostitution poses significant challenges in law enforcement. Although the TPPO Law and the ITE Law provide a legal framework to prosecute perpetrators, their implementation in the field faces various obstacles, including a lack of understanding of digital technology by law enforcement officers, as well as limitations in collecting valid electronic evidence. This study emphasizes the need for increased capacity and training for law enforcement officers, as well as more specific regulatory updates to deal with the rapidly growing cybercrime. The conclusion of this study is that the phenomenon of online prostitution through the MiChat application is a complex form of crime and requires a comprehensive legal approach. Synergy is needed between various parties, including the government, law enforcement officers, and the community, to overcome this challenge. In addition, strengthening regulations and increasing digital literacy in the community are key to preventing the misuse of technology for illegal purposes.